Teachers' beliefs about interculturalism in class PERMIT case preliminar research findings - Juliana Raffaghelli (Pensa MultiMedia, 2015)
Research about teachers' professionalism has driven attention in the last years. This is due probably to the fact that an increasing attention to teachers as key players in educational changing, linked to the new centrality of education and training as foundamental pieces of economical and social development. The discussion about teachers' professionalism started to delineate it own field within educational research from the 60's (and particularly 70's). Since then, tendencies have changed from objectivist models (through the observation of teachers at work) to consider their cognitive and metacognitive operation when planning their own work, to a complete introduction of their subjectivity as individuals deeply involved in creating their professional identity. The new perspectives of research on teachers' professionalism involve hence the exploration of experiences, beliefs, images and social representations of teaching and learning, connected to specific cultural contexts. This article attempts to introduce a study on teachers' values, opinions and beliefs, about intercultural dialogue in class, as part of a preliminar research addressing further experimental teachers' training activities.